Intracycle interference in the interaction of laser and electron beams - Morimoto, Yuya; Hommelhoff, Peter (Physical Review Research, 2020)
A high-energy electron beam coupled to an optical field experiences a quantized energy modulation by multiples of the photon energy, originating from the temporal periodicity of the optical field by virtue of intercycle interference. Here we investigate the quantum interference occurring at shorter timescales, namely, within half an optical cycle, which is called intracycle interference. We show that the sub-half-cycle energy and phase modulation are imprinted into and largely modulate electron energy spectra regardless of the laser pulse duration. The intracycle effect is universal, meaning that it shows up for almost any electron velocity and optical wavelength. It thus facilitates coherent control of free-electron beams in microscopes or accelerators with a resolution of below an optical cycle, i.e., on attosecond timescales. The results obtained also apply to multiphoton and attosecond physics in atoms, molecules, and solids.<br
Keywords: attosecond physics; energy modulation of electron beams; quantum interference